2017
DOI: 10.1080/02701960.2017.1281805
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a video-based aging services technology education program for health care professionals

Abstract: Health care professionals (HCPs) are a critical source of recommendations for older adults. Aging services technologies (ASTs), which include devices to support the health-care needs of older adults, are underutilized despite evidence for improving functional outcomes and safety and reducing caregiver burden and health costs. This study evaluated a video-based educational program aimed at improving HCP awareness of ASTs. Sixty-five HCPs viewed AST videos related to medication management, daily living, and memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The study suggested the success of the video program and concluded an increase in the objective enhancement of AST awareness among hospital employees [46]. Regarding basic perception, the awareness videos significantly impacted the participants' perceptions and produced positive changes across all three statements, with the average increasing from 74.7% to 87.1%.…”
Section: Influence Of Awareness Videos On Miot Knowledge and Perceptionsmentioning
confidence: 86%
See 1 more Smart Citation
“…The study suggested the success of the video program and concluded an increase in the objective enhancement of AST awareness among hospital employees [46]. Regarding basic perception, the awareness videos significantly impacted the participants' perceptions and produced positive changes across all three statements, with the average increasing from 74.7% to 87.1%.…”
Section: Influence Of Awareness Videos On Miot Knowledge and Perceptionsmentioning
confidence: 86%
“…The comparison literature is scarce, but limited available research supports these findings. [46] conducted a study with hospital care professionals to evaluate the effectiveness of an educational video program developed to increase Aging Service Technology (AST) knowledge.…”
Section: Influence Of Awareness Videos On Miot Knowledge and Perceptionsmentioning
confidence: 99%
“…• Absence of educational programs to train users and personnel the supply or distribution of services is in place. The accessibility of DAT cannot be guaranteed, and the use of products and services depends on socio-economic, technical, and cultural variables as well as geographical differences [14,15,[17][18][19][20][21][22][23][24][25][26][27].…”
Section: Representatives From Interest Organizationsmentioning
confidence: 99%
“…From diversity in the infrastructure to virtual networks (adapted from Vimarlund V., Kock S. 2016) [15]. through monitoring or follow-up, or to detect and respond to potential emergencies), and to enable individuals to remain active, socially connected, and independent [15,[26][27][28][29][30][31][32][33] (see Table 3).…”
Section: Representatives From Interest Organizationsmentioning
confidence: 99%